National Health Insurance Scheme: Internal and External Barriers in the Use of Reproductive Health Services among Women - Martha, Evi; Lestari, Herna; Zulfa, Resvi Siti; Sopamena, Yoslien (UI Scholars Hub, 2021)
Lack of familiarity among the community, medical workers, and administrative staff regarding reproductive health services covered by Badan Penyelenggara Jaminan Sosial (BPJS) or the National Health Insurance (NHI) in Indonesia remained a problem. Therefore, this resulted in sub-optimal use of the medical services, as shown by surveys from the Women's Health Foundation for three consecutive years (2015-2017). This qualitative study was conducted with a Rapid Assessment Procedure design in three cities within Indonesia: Padang Pariaman, Manado, and Kupang. Data were collected through IDIs (n = 47informants) and 6 FGDs (7 persons/group). Participants also consisted of NHI RHS users (mothers and young women), administrative officers at health facilities, medical services providers, and officials related to the NHI assistance. Data were managed using NVivo version 2.0 software, accompanied by thematic analysis. The internal barriers in NHI use included inadequate knowledge of RHS covered by NHI, and a culture of shame in informants. External barriers included additional costs for medicines not covered by NHI, the dissatisfaction of health services provided by medical workers, busy work and household activities, and lack of women's role in decision-making within families, which related to reproductive wellness.